A nano-scale tantalum-tungsten alloy powder and a method for preparing the same
Patent Information
- Application Number
- CN202410462376.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-17
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2044-04-17
AI Technical Summary
该方法先将仲钨酸铵与氯化钽原料共沉淀制备前驱体粉末,然后经加热制备钽钨复合氧化物粉末,再通过自蔓延反应,使得反应过程中钽钨复合氧化物粉末被镁还原后充分接触,进而合金化制备得到纳米级钽钨合金粉末,解决了现有技术中纳米级钽钨合金粉末制备工艺复杂、粉末粒度难以控制等问题
[0016] 1. This invention involves mixing ammonium paratungstate and tantalum chloride raw materials in solution, then adding ammonia water for co-precipitation to form a precursor powder. The precursor powder is then heated and kept at a constant temperature to obtain tantalum-tungsten composite oxide powder. Through a self-propagating reaction and precise control of the reaction conditions, the tantalum-tungsten composite oxide powder is fully contacted after being reduced by magnesium during the reaction, and then alloyed to prepare nano-sized tantalum-tungsten alloy powder. This invention solves the problems of complex preparation process and difficulty in controlling powder particle size in the prior art for nano-sized tantalum-tungsten alloy powder, and is therefore beneficial for obtaining tantalum-tungsten alloy with high strength and toughness.
Abstract
Description
Technical Field
[0001] This invention belongs to the field of powder metallurgy technology, specifically relating to a nanoscale tantalum-tungsten alloy powder and its preparation method. Background Technology
[0002] Tantalum (Ta) is the 49th most abundant rare metal on Earth. It has a body-centered cubic (BCC) crystal structure and a high melting point (2996℃) and density (16.6 g / cm³). 3 Tantalum possesses excellent thermal conductivity, electrical conductivity, and biocompatibility, and exhibits no phase transformation during deformation, recovery, and recrystallization over a wide temperature range. Adding tungsten (W) to tantalum provides excellent solid solution strengthening, forming high-strength tantalum-tungsten solid solution alloys, with strength increasing significantly with increasing tungsten content. Tantalum-tungsten alloys have attracted considerable attention due to their high performance at high temperatures and high deformation rates, making them indispensable materials in aerospace, nuclear industry, and high-temperature technology fields.
[0003] Tantalum-tungsten alloys are generally prepared using either smelting or powder metallurgy. Among smelting methods, vacuum electron beam melting is the best refining method, effectively removing various impurities from the material, especially those with low melting points. However, because vacuum electron beam melting results in coarse ingot grains, which is detrimental to further processing, smelting is generally used to prepare tantalum-tungsten alloy bars. Powder metallurgy, on the other hand, can produce materials without preferred orientation, so it can be used. Common methods include mechanical alloying, mechanical grinding, chemical vapor deposition, redox reactions, and sol-gel processes to prepare tantalum-tungsten alloys.
[0004] With the rapid development of high-temperature technology, the performance requirements for structural materials are becoming increasingly stringent. Preparing stronger, higher-performance tantalum-tungsten alloys to ensure reliability under extreme service conditions has become an important research direction. Therefore, exploring a reasonable, efficient, and low-cost method to successfully prepare nanoscale tantalum-tungsten alloy powder has significant practical application value. Summary of the Invention
[0005] The technical problem to be solved by this invention is to provide a method for preparing nanoscale tantalum-tungsten alloy powder, addressing the shortcomings of the prior art. This method first prepares a precursor powder by co-precipitating ammonium paratungstate and tantalum chloride. Then, a tantalum-tungsten composite oxide powder is prepared by heating. Next, through a self-propagating reaction, the tantalum-tungsten composite oxide powder is reduced by magnesium and fully contacted, thereby alloying to obtain nanoscale tantalum-tungsten alloy powder. This method solves the problems of complex preparation processes and difficulty in controlling powder particle size in the prior art.
[0006] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is: a method for preparing nano-scale tantalum-tungsten alloy powder, characterized in that the method includes the following steps:
[0007] Step 1: Preparation of precursor powder: Under the condition of electromagnetic stirring in a water bath, ammonium paratungstate is dissolved in deionized water to prepare an aqueous solution of ammonium paratungstate, and tantalum chloride is dissolved in anhydrous ethanol to prepare an anhydrous ethanol solution of tantalum chloride. Then, the anhydrous ethanol solution of tantalum chloride is added dropwise to the aqueous solution of ammonium paratungstate to obtain a mixed solution. Ammonia water is then added dropwise to the mixed solution. After standing and allowing the supernatant to be removed, the solution is dried to obtain the precursor powder.
[0008] Step 2, Preparation of tantalum-tungsten composite oxide powder: The precursor powder obtained in Step 1 is heated and kept at a constant temperature in air and then cooled in a furnace to obtain tantalum-tungsten composite oxide powder.
[0009] Step 3, Self-propagating reaction: The tantalum-tungsten composite oxide powder obtained in Step 2 is uniformly mixed with magnesium powder and sodium chloride and then subjected to a self-propagating reaction under argon or vacuum conditions. After furnace cooling, the self-propagating reaction product is dissolved in nitric acid and allowed to stand to precipitate. After removing the supernatant, it is dried to obtain nano-sized tantalum-tungsten alloy powder.
[0010] The above-mentioned method for preparing nano-scale tantalum-tungsten alloy powder is characterized in that: the temperature of the water bath electromagnetic stirring condition in step one is 60°C; the ammonium paratungstate aqueous solution is prepared at a ratio of 0.05g to 1g of ammonium paratungstate dissolved in 20mL to 120mL of deionized water; the anhydrous tantalum chloride ethanol solution is prepared at a ratio of 0.05g to 2g of tantalum chloride dissolved in 3mL to 90mL of anhydrous ethanol; the dripping rate is 0.1mL / s to 1mL / s; the ammonia water is added dropwise until the pH of the mixed solution is 9.5 to 12.5; and the drying temperature is 120°C.
[0011] The above-mentioned method for preparing nano-scale tantalum-tungsten alloy powder is characterized in that the heating and holding temperature in step two is 800℃~1000℃ and the time is 0.5h~5h.
[0012] The above-mentioned method for preparing nano-scale tantalum-tungsten alloy powder is characterized in that the mass ratio of the tantalum-tungsten composite oxide powder to magnesium powder and sodium chloride in step three is 1:3-20:5-50.
[0013] The above-mentioned method for preparing nanoscale tantalum-tungsten alloy powder is characterized in that the temperature of the self-propagating reaction in step three is 900℃~1100℃, and the time is 2h~8h; the drying temperature is 120℃. This invention, by controlling the temperature and time of the self-propagating reaction, utilizes heating to provide a driving force for the nucleation of tantalum-tungsten alloy nanoparticles, avoiding insufficient driving force due to excessively low temperatures (resulting in incomplete nucleation of the nanoparticles) and excessively high temperatures (resulting in the volatilization of magnesium and insufficient reduction of the tantalum-tungsten composite oxide powder), thereby ensuring the acquisition of nanoscale tantalum-tungsten alloy powder.
[0014] In addition, the present invention discloses a nano-sized tantalum-tungsten alloy powder prepared by the above method, characterized in that the particle size of the nano-sized tantalum-tungsten alloy powder is 10nm to 160nm, the average particle size is not more than 70nm, the microstructure is a single phase of tantalum-tungsten alloy, and the atomic percentage of tantalum is 0.5% to 95%.
[0015] Compared with the prior art, the present invention has the following advantages:
[0016] 1. This invention involves mixing ammonium paratungstate and tantalum chloride raw materials in solution, then adding ammonia water for co-precipitation to form a precursor powder. The precursor powder is then heated and kept at a constant temperature to obtain tantalum-tungsten composite oxide powder. Through a self-propagating reaction and precise control of the reaction conditions, the tantalum-tungsten composite oxide powder is fully contacted after being reduced by magnesium during the reaction, and then alloyed to prepare nano-sized tantalum-tungsten alloy powder. This invention solves the problems of complex preparation process and difficulty in controlling powder particle size in the prior art for nano-sized tantalum-tungsten alloy powder, and is therefore beneficial for obtaining tantalum-tungsten alloy with high strength and toughness.
[0017] 2. This invention improves the nucleation rate of the precursor powder and reduces its particle size by controlling the rate at which anhydrous tantalum chloride ethanol solution is dropped into ammonium paratungstate aqueous solution, thereby ensuring that nanoscale tantalum-tungsten alloy powder is obtained through subsequent self-propagating reaction.
[0018] 3. In this invention, tantalum-tungsten composite oxide powder is mixed with magnesium powder and sodium chloride and then subjected to a self-propagating reaction. Since all three are powder particles with large surface areas, they can fully contact each other. By controlling the mass ratio of the three, the magnesium powder can fully reduce the tantalum-tungsten composite oxide powder. At the same time, since the self-propagating reaction process releases a large amount of heat, excessive heat energy will cause the formed tantalum-tungsten alloy powder to grow and increase in size beyond the nanometer scale. Therefore, sodium chloride (melting point of 801℃) is added to convert into molten sodium chloride during the reaction process and absorb heat, thereby keeping the temperature of the self-propagating reaction within a suitable range and ensuring that nano-sized tantalum-tungsten alloy powder is obtained.
[0019] 4. This invention achieves a chemical reaction between tantalum and tungsten through a self-propagating reaction, resulting in nanoscale tantalum-tungsten alloy powder with uniform chemical composition. Rather than forming tantalum-tungsten composite powder solely through physical interaction, this nanoscale tantalum-tungsten alloy powder exhibits a single-phase structure, i.e., complete alloying. During its sintering process, this fully alloyed nanoscale tantalum-tungsten alloy powder does not require element diffusion and homogenization; it only needs to form sintering neck bonds between the powder particles. This facilitates lowering the sintering temperature and reducing the sintering holding time.
[0020] 5. The nano-sized tantalum-tungsten alloy powder prepared by this invention has a particle size of 10nm to 160nm, with an average particle size of no more than 70nm. It has high sintering activity, and the alloy products sintered from it have advantages such as ultrafine grains and high performance, and have good application prospects.
[0021] 6. The preparation process of the present invention is simple, easy to operate, and low in cost, making it suitable for large-scale industrial production.
[0022] The technical solution of the present invention will be further described in detail below through embodiments. Detailed Implementation
[0023] Example 1
[0024] This embodiment includes the following steps:
[0025] Step 1: Preparation of precursor powder: Under electromagnetic stirring in a water bath at 60℃, 0.5g of ammonium paratungstate was dissolved in 70mL of deionized water to prepare an aqueous solution of ammonium paratungstate. 1.4g of tantalum chloride was dissolved in 80mL of anhydrous ethanol to prepare an anhydrous ethanol solution of tantalum chloride. The anhydrous ethanol solution of tantalum chloride was then added dropwise to the aqueous solution of ammonium paratungstate at a rate of 0.5mL / s to obtain a mixed solution. Ammonia was then added dropwise to the mixed solution until the pH of the mixed solution reached 11. After standing to precipitate and removing the supernatant, the solution was dried at 120℃ to obtain the precursor powder.
[0026] Step 2, Preparation of tantalum-tungsten composite oxide powder: The precursor powder obtained in Step 1 is heated to 910℃ in air atmosphere and held for 2.5h, then furnace cooled to obtain tantalum-tungsten composite oxide powder;
[0027] Step 3, Self-propagating reaction: The tantalum-tungsten composite oxide powder obtained in Step 2 is uniformly mixed with magnesium powder and sodium chloride in a mass ratio of 1:9:26. The mixture is then heated to 1020℃ under vacuum and held for 5 hours to carry out a self-propagating reaction. After the furnace cools, the self-propagating reaction product is dissolved in nitric acid and allowed to settle. After removing the supernatant, the mixture is dried at 120℃ to obtain nano-sized tantalum-tungsten alloy powder.
[0028] Testing revealed that the nanoscale tantalum-tungsten alloy powder prepared in this embodiment has a particle size of 16 nm to 144 nm, an average particle size of no more than 66 nm, a microstructure of a single phase of tantalum-tungsten alloy, and an atomic percentage of tantalum of 44.29%.
[0029] Example 2
[0030] The difference between this embodiment and Embodiment 1 is as follows: In step one, 0.1g of ammonium paratungstate is dissolved in 40mL of deionized water to prepare an aqueous solution of ammonium paratungstate, and 0.9g of tantalum chloride is dissolved in 45mL of anhydrous ethanol to prepare an anhydrous ethanol solution of tantalum chloride. Then, the anhydrous ethanol solution of tantalum chloride is added dropwise to the aqueous solution of ammonium paratungstate at a rate of 0.9mL / s to obtain a mixed solution. Ammonia water is then added dropwise to the mixed solution until the pH of the mixed solution is 10.5. In step three, the mass ratio of tantalum-tungsten composite oxide powder to magnesium powder and sodium chloride is 1:19:49.
[0031] Testing revealed that the nanoscale tantalum-tungsten alloy powder prepared in this embodiment has a particle size of 12nm to 158nm, an average particle size of no more than 48nm, a microstructure of a single phase of tantalum-tungsten alloy, and an atomic percentage of tantalum of 85.8%.
[0032] Example 3
[0033] The difference between this embodiment and Embodiment 1 is as follows: In step one, 0.8g of ammonium paratungstate is dissolved in 110mL of deionized water to prepare an aqueous solution of ammonium paratungstate, and 0.2g of tantalum chloride is dissolved in 10mL of anhydrous ethanol to prepare an anhydrous ethanol solution of tantalum chloride. Then, the anhydrous ethanol solution of tantalum chloride is added dropwise to the aqueous solution of ammonium paratungstate at a rate of 0.2mL / s to obtain a mixed solution. Ammonia water is then added dropwise to the mixed solution until the pH of the mixed solution is 9.7. In step three, the mass ratio of tantalum-tungsten composite oxide powder to magnesium powder and sodium chloride is 1:4:6.
[0034] Testing revealed that the nanoscale tantalum-tungsten alloy powder prepared in this embodiment has a particle size of 11 nm to 155 nm, an average particle size of no more than 53 nm, a single-phase tantalum-tungsten alloy microstructure, and an atomic percentage of tantalum of 10.2%.
[0035] Example 4
[0036] The difference between this embodiment and Embodiment 1 is that in step one, 0.06g of ammonium paratungstate is dissolved in 22mL of deionized water to prepare an aqueous solution of ammonium paratungstate.
[0037] Testing revealed that the nanoscale tantalum-tungsten alloy powder prepared in this embodiment has a particle size of 13 nm to 156 nm, an average particle size of no more than 55 nm, a microstructure of a single phase of tantalum-tungsten alloy, and an atomic percentage of tantalum of 11.1%.
[0038] Example 5
[0039] The difference between this embodiment and Embodiment 1 is that in step one, 0.06g of tantalum chloride is dissolved in 4mL of anhydrous ethanol to prepare an anhydrous tantalum chloride ethanol solution.
[0040] Testing revealed that the nanoscale tantalum-tungsten alloy powder prepared in this embodiment has a particle size of 12nm to 150nm, an average particle size of no more than 63nm, a microstructure of a single phase of tantalum-tungsten alloy, and an atomic percentage of tantalum of 0.6%.
[0041] Example 6
[0042] The difference between this embodiment and embodiment 4 is that in step one, 1.95g of tantalum chloride was dissolved in 88mL of anhydrous ethanol to prepare an anhydrous tantalum chloride ethanol solution.
[0043] Testing revealed that the nanoscale tantalum-tungsten alloy powder prepared in this embodiment has a particle size of 15 nm to 146 nm, an average particle size of no more than 43 nm, a microstructure of a single phase of tantalum-tungsten alloy, and an atomic percentage of tantalum of 94.2%.
[0044] Example 7
[0045] The difference between this embodiment and Embodiment 1 is that in step one, anhydrous tantalum chloride ethanol solution is added dropwise to ammonium paratungstate aqueous solution at a rate of 0.1 mL / s to obtain a mixed solution.
[0046] Testing revealed that the nanoscale tantalum-tungsten alloy powder prepared in this embodiment has a particle size of 18 nm to 156 nm, an average particle size of no more than 38 nm, a microstructure of a single phase of tantalum-tungsten alloy, and an atomic percentage of tantalum of 9.2%.
[0047] Example 8
[0048] The difference between this embodiment and Embodiment 1 is that in step one, anhydrous tantalum chloride ethanol solution is added dropwise to ammonium paratungstate aqueous solution at a rate of 0.9 mL / s to obtain a mixed solution.
[0049] Testing revealed that the nanoscale tantalum-tungsten alloy powder prepared in this embodiment has a particle size of 21 nm to 158 nm, an average particle size of no more than 61 nm, a microstructure of a single phase of tantalum-tungsten alloy, and an atomic percentage of tantalum of 33.2%.
[0050] Example 9
[0051] The difference between this embodiment and Embodiment 1 is that in step one, ammonia water is added dropwise to the mixed solution until the pH of the mixed solution is 9.6.
[0052] Testing revealed that the nanoscale tantalum-tungsten alloy powder prepared in this embodiment has a particle size of 31 nm to 125 nm, an average particle size of no more than 51 nm, a single-phase tantalum-tungsten alloy microstructure, and an atomic percentage of tantalum of 64.3%.
[0053] Example 10
[0054] The difference between this embodiment and Embodiment 1 is that in step one, ammonia water is added dropwise to the mixed solution until the pH of the mixed solution is 12.4.
[0055] Testing revealed that the nanoscale tantalum-tungsten alloy powder prepared in this embodiment has a particle size of 11 nm to 145 nm, an average particle size of no more than 44 nm, a microstructure of a single phase of tantalum-tungsten alloy, and an atomic percentage of tantalum of 71.1%.
[0056] Example 11
[0057] The difference between this embodiment and Embodiment 1 is that in step two, the precursor powder is heated to 810°C in air and held for 0.6 hours before being furnace cooled.
[0058] Testing revealed that the nanoscale tantalum-tungsten alloy powder prepared in this embodiment has a particle size of 12nm to 133nm, an average particle size of no more than 31nm, a microstructure of a single phase of tantalum-tungsten alloy, and an atomic percentage of tantalum of 23.9%.
[0059] Example 12
[0060] The difference between this embodiment and Embodiment 1 is that in step two, the precursor powder is heated to 980°C in air and held for 4.8 hours before being furnace cooled.
[0061] Testing revealed that the nanoscale tantalum-tungsten alloy powder prepared in this embodiment has a particle size of 10 nm to 145 nm, an average particle size of no more than 48 nm, a microstructure of a single phase of tantalum-tungsten alloy, and an atomic percentage of tantalum of 31.6%.
[0062] Example 13
[0063] The difference between this embodiment and Embodiment 1 is that in step three, the obtained tantalum-tungsten composite oxide powder is uniformly mixed with magnesium powder and sodium chloride in a mass ratio of 1:3.2:5.2, and then heated to 920°C under vacuum conditions and kept at that temperature for 2 hours to carry out a self-propagating reaction.
[0064] Testing revealed that the nanoscale tantalum-tungsten alloy powder prepared in this embodiment has a particle size of 22 nm to 153 nm, an average particle size of no more than 61 nm, a microstructure of a single phase of tantalum-tungsten alloy, and an atomic percentage of tantalum of 34.3%.
[0065] Example 14
[0066] The difference between this embodiment and Embodiment 1 is that in step three, the obtained tantalum-tungsten composite oxide powder is uniformly mixed with magnesium powder and sodium chloride in a mass ratio of 1:19.7:49.6 and then heated to 1080°C under an argon atmosphere for 7 hours to carry out a self-propagating reaction.
[0067] Testing revealed that the nanoscale tantalum-tungsten alloy powder prepared in this embodiment has a particle size of 20 nm to 156 nm, an average particle size of no more than 21 nm, a microstructure of a single phase of tantalum-tungsten alloy, and an atomic percentage of tantalum of 62.2%.
[0068] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention in any way. Any simple modifications, alterations, and equivalent changes made to the above embodiments based on the inventive essence shall still fall within the protection scope of the present invention.
Claims
1. A method for preparing nanoscale tantalum-tungsten alloy powder, characterized in that, The method includes the following steps: Step 1: Preparation of precursor powder: Under water bath electromagnetic stirring conditions, ammonium paratungstate is dissolved in deionized water to prepare an aqueous solution of ammonium paratungstate, and tantalum chloride is dissolved in anhydrous ethanol to prepare an anhydrous tantalum chloride ethanol solution. The anhydrous tantalum chloride ethanol solution is then added dropwise to the ammonium paratungstate aqueous solution to obtain a mixed solution. Ammonia is then added dropwise to the mixed solution, and after standing to precipitate and removing the supernatant, the solution is dried to obtain the precursor powder. The temperature of the water bath electromagnetic stirring conditions is 60℃. The ammonium paratungstate aqueous solution is prepared at a ratio of 0.05g~1g ammonium paratungstate dissolved in 20mL~120mL deionized water, and the anhydrous tantalum chloride ethanol solution is prepared at a ratio of 0.05g~2g tantalum chloride dissolved in 3mL~90mL anhydrous ethanol. The dropwise addition rate is 0.1mL / s~1mL / s. Ammonia is added dropwise until the pH of the mixed solution is 9.5~12.
5. The drying temperature is 120℃. Step 2, Preparation of tantalum-tungsten composite oxide powder: The precursor powder obtained in Step 1 is heated and kept at a constant temperature in air and then cooled in a furnace to obtain tantalum-tungsten composite oxide powder. Step 3, Self-propagating reaction: The tantalum-tungsten composite oxide powder obtained in Step 2 is uniformly mixed with magnesium powder and sodium chloride, and then subjected to a self-propagating reaction under argon or vacuum conditions. After furnace cooling, the self-propagating reaction product is dissolved in nitric acid, allowed to stand and precipitate, the supernatant is removed and then dried to obtain nano-sized tantalum-tungsten alloy powder; the mass ratio of the tantalum-tungsten composite oxide powder to magnesium powder and sodium chloride is 1:3~20:5~50; the temperature of the self-propagating reaction is 900℃~1100℃, and the time is 2h~8h.
2. The method for preparing nanoscale tantalum-tungsten alloy powder according to claim 1, characterized in that, The heating and heat preservation temperature in step two is 800℃~1000℃, and the time is 0.5h~5h.
3. The method for preparing nanoscale tantalum-tungsten alloy powder according to claim 1, characterized in that, The drying temperature in step three is 120°C.
4. A nanoscale tantalum-tungsten alloy powder prepared by the method according to any one of claims 1 to 3, characterized in that, The nanoscale tantalum-tungsten alloy powder has a particle size of 10nm~160nm, with an average particle size of no more than 70nm. The microstructure is a single phase of tantalum-tungsten alloy, and the atomic percentage of tantalum is 0.5%~95%.
Citation Information
Patent Citations
Nanoscale refractory high-entropy alloy powder and preparation method thereof
CN118321567A